Landslide hazard assessment of the Norak region of Tadjikistan - B. Kh. Muminov; I. K. Fomenko; O. N. Sirotkina (Известия высших учебных заведений: Геология и разведка, 2022)
Introduction. The application of geographic information system (GIS) technologies is a promising technology for mapping and evaluating landslide hazards. At present, satellite-based terrestrial sensing is widely used. Satellite images make it possible not only to identify individual landslides, particularly in hard-to-reach areas, but also to identify those locations where landslide processes have manifested, are manifesting and may manifest themselves in the future.Aim. Mapping of the present landslide propagation in the territory of the Norak region of Tajikistan using satellite imaging and GIS.Materials and methods. In the course of the study, maps of landslide propagation were compiled both automatically and manually. An analysis of the results of previous studies and interpretations of satellite images was conducted. Digital models of the relief, as well as topographic, geomorphological, engineering and geological maps, were investigated.Results. A detailed map of landslide phenomena was compiled in the GIS format and a database of landslide phenomena was created for the first time for the territory of the Norak region of the Republic of Tajikistan.Conclusions. The conducted zoning showed that, out of the total landslide number, 24%, 36%, 10%, 18% and 12% correspond to very small, small, medium, large, and very large landslides, respectively. The landslide processes are developed across the area of 2601×104 m2, which accounts for the 4% of the total area of the district. The results demonstrate that the approach used in this study may be applicable to the landslide hazard assessment in hard-to-reach and poorly studied regions.